Astral Iconography, Star Deities and the Celtic "Otherworld" in the Roman West - Olivares Pedreño, Juan Carlos (’Ilu. Revista de Ciencias de las Religiones, 2019)
In this paper, we study astral symbols such as wheels, swastikas, triskelions and lunar crescents when they appear in votive offerings dedicated to Celtic divinities in the Western regions of the Roman Empire. From the presence of these symbols in numerous funeral steles and in archaeological contexts related to death in areas of intense Celtic cultural presence, we formulate the hypothesis that the Celtic divinities related to these symbols throughout the Roman West have an astral character and, in addition, a mythological and ritual connection with the funerary world.